On greedy algorithms for binary de Bruijn sequences - Chang, Zuling; Ezerman, Martianus Frederic; Fahreza, Adamas Aqsa (Applicable algebra in engineering, communication and computing, 2022)
We propose a general greedy algorithm for binary de Bruijn sequences, called Generalized Prefer-Opposite Algorithm, and its modifications. By identifying specific feedback functions and initial states, we demonstrate that most previously-known greedy algorithms that generate binary de Bruijn sequences are particular cases of our algorithm.